Analisis Akuntansi Anggaran Pendapatan Belanja Daerah Dalam Laporan Realisasi Anggaran Dan Kesesuaian Panyajian Laporan Terhadap PSAP 02 Pada Badan Pengelola Keuangan Dan Aset Daerah Kota Medan - Nurul Aini Siregar; Saparuddin Siregar; Wahyu Syarvina (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This research aims to determine the presentation of the Medan City Government budget realization report prepared by the Medan City BPKAD with reference to PSAP number 02 concerning budget realization reports regulated in Government Regulation Number 71 concerning government accounting standards. The types of data used in this research are primary data and secondary data. Data collection techniques were carried out using interview techniques, observation and documentation studies. The data analysis method used is descriptive qualitative with a checklist. This research was conducted at the Regional Financial and Asset Management Agency of Medan City which is located at Jalan Captain Maulana Lubis No. 2 Medan, North Sumatra. The results of this research show that the level of conformity in implementing PSAP No.02 PP No.71 of 2010 reaches 100% using the Dean J.Champion formula. This means that the implementation of the Budget Realization Report within the Medan city government is in accordance with PSAP No.02 PP No. 71 of 2010.